A study of typhoid fever in five asian countries: disease burden and implications for controls - R Leon Ochiai; Camilo J Acosta; M Carolina Danovaro-Holliday; Dong Baiqing; Sujit K Bhattacharya; Magdarina D Agtini; Zulfiqar A Bhutta; Do Gia Canh; Mohammad Ali; Seonghye Shin; John Wain; Anne-Laure Page; et al. (Bulletin of the World Health Organization, 2008)
OBJECTIVE: To inform policy-makers about introduction of preventive interventions against typhoid, including vaccination. METHODS: A population-based prospective surveillance design was used. Study sites where typhoid was considered a problem by local authorities were established in China, India, Indonesia, Pakistan and Viet Nam. Standardized clinical, laboratory, and surveillance methods were used to investigate cases of fever of > 3 days' duration for a one-year period. A total of 441 435 persons were under surveillance, 159 856 of whom were aged 5-15 years. FINDINGS: A total of 21 874 episodes of fever were detected. Salmonella typhi was isolated from 475 (2%) blood cultures, 57% (273/475) of which were from 5-15 year-olds. The annual typhoid incidence (per 100 000 person years) among this age group varied from 24.2 and 29.3 in sites in Viet Nam and China, respectively, to 180.3 in the site in Indonesia; and to 412.9 and 493.5 in sites in Pakistan and India, respectively. Altogether, 23% (96/413) of isolates were multidrug resistant (chloramphenicol, ampicillin and trimethoprim-sulfamethoxazole). CONCLUSION: The incidence of typhoid varied substantially between sites, being high in India and Pakistan, intermediate in Indonesia, and low in China and Viet Nam. These findings highlight the considerable, but geographically heterogeneous, burden of typhoid fever in endemic areas of Asia, and underscore the importance of evidence on disease burden in making policy decisions about interventions to control this disease.